A new surface vibration extrusion process for surface densification and improvement of properties in powder metallurgical steel. (April 2022) - Li, Xiao; Guo, Biao; Jian, Jie; Ao, Jinqing; Tang, Qifeng; Song, Jiupeng; Zhang, Yu
Graphical abstract: Highlights: Surface vibration extrusion was proposed to densify the surface of powder metallurgical steel. Enhanced surface densification and reduced extrusion load were observed by applying surface vibration extrusion. The mechanism for vibration assistance enhancing the surface densification was revealed via EBSD examination. High surface-densified layer and superior mechanical properties of the surface vibration extruded samples were achieved. Abstract: Selective surface densification (SSD) can greatly improve the mechanical properties of powder metallurgical (P/M) parts with low additional costs. This work proposes a new surface vibration extrusion process to make up for some drawbacks of the existing SSD processes as far as possible. The surface densification effect and mechanism, as well as mechanical properties of the surface extruded P/M Fe-Mo-Cu-C steel with and without vibration assistance, are comparatively investigated. Following a small surface extrusion processing via a simple extrusion die, the surface of the vibration extruded P/M steel is more thoroughly and uniformly densified under a lower extrusion load when compared with the directly extruded P/M steel. This can be attributed to the vibration assistance facilitating the dislocation motion and metal flow. The high surface-densified layer is achieved, with depth up to 530 μm slightly superior to some commercial SSD parts. Moreover, approximately twice the surface hardness is obtained compared with the hardness before the extrusion. Lastly, superior friction and wear properties are achieved. Results indicate that surface vibration extrusion can be used as a promising process for the surface densification of P/M parts.